Sistem Pendukung Keputusan Untuk Pemilihan Buruh Harian Lepas Menjadi Karyawan Tetap Menggunakan Metode Profile Matching (Studi Kasus : PT. Nafasindo) - Haidi Haidi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
A daily freelance worker is someone who works alone and is not committed to a certain long-term business owner. Temporary daily workers also have obligations that must be fulfilled as something that must be done if the day laborer wants to get his salary, by doing work with a large target without taking into account working hours, this is the only obligation that must be done because casual daily laborers do not bound to a permanent work agreement where usually in the permanent employment agreement the worker must obey every regulation set by the business owner both the company and individual business. Permanent employees are someone who works with the conditions made by the company in work and all work activities have been arranged and the payroll process is carried out with the basic salary set by the company monthly. So from that the plantations of PT. Nafasindo make an assessment in choosing daily burh employees to become permanent employees by making decisions based on the judgments made in the field. thus the need for decision making such as a computerized decision support system so that decision making can be done quickly and accurately. thus this decision support system uses a profile matching or profile matching method which will be used between a fixed profile and a casual day laborer profile with a review process on the criteria that will be set to fulfill permanent employment.